2007
DOI: 10.19030/rbis.v11i3.4412
|View full text |Cite
|
Sign up to set email alerts
|

Team Transformational Leadership, Trust, Satisfaction, And Commitment: The Testing Of A Structural Equation Model In Software Development Teams

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…We found that there are positive and significant intercorrelations among transformational leadership, organizational commitment, organizational trust and job satisfaction. The results of this study are consistent with previous exploratory studies that examined the same relationships (Meyer and Allen, ; Turnley and Feldman, ; Kent and Chelladurai, ; Meyer and Herscovitch, ; Lagomarsino and Cardona, ; Avolio et al ., ; Chen, ; Saygun, et al ., ; Lee, ; Liu, ; Walumbwa et al ., ; Hsu, ; Hsu and Mujtaba, ; Tanner, ; Wong, ; Laschinger, ; Tanner and Sezen, ; Wolfram and Mohr, ; Lee et al ., ; Lonial, et al ., ; Wood and Menezes, ). Several previous research related to the results of our study are presented subsequently in summary.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there are positive and significant intercorrelations among transformational leadership, organizational commitment, organizational trust and job satisfaction. The results of this study are consistent with previous exploratory studies that examined the same relationships (Meyer and Allen, ; Turnley and Feldman, ; Kent and Chelladurai, ; Meyer and Herscovitch, ; Lagomarsino and Cardona, ; Avolio et al ., ; Chen, ; Saygun, et al ., ; Lee, ; Liu, ; Walumbwa et al ., ; Hsu, ; Hsu and Mujtaba, ; Tanner, ; Wong, ; Laschinger, ; Tanner and Sezen, ; Wolfram and Mohr, ; Lee et al ., ; Lonial, et al ., ; Wood and Menezes, ). Several previous research related to the results of our study are presented subsequently in summary.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons why SDPs are often outsourced to international countries is because of lower costs, the availability of resources with the necessary skills, especially if it is a new technology, and also to speed up the development process of the application. It is noted that soft skills are more important than technical skills in a SDP [28].…”
Section: The Difference Between Software Development Projects and mentioning
confidence: 99%
“…It has in fact been observed that commitment to a specific target, for instance one's own team, would be a better predictor of behaviours relevant to that target than a general organizational commitment (Herscovitch & Meyer, 2002). Hsu and Mujtaba (2011), for example, focused their attention on team level commitment. Bass (1999) suggested that there is a clear need for better understanding how transformational leadership influences employees' work-related attitudes, such as affective team commitment.…”
Section: Transformational Leadership and Affective Team Commitmentmentioning
confidence: 99%